UJI EMPAT JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI KERITING (Capsicum annum L.) - Andayani dan La Sarido (Universitas 17 Agustus 1945 Samarinda, 2013)
The study aims to determine the best type of manure and suitable for the growth of curly chilli. It carried out at Damai Sub District of West Kutai District. This study using randomized completely design consisting of four treatments. The treatment covered cow manure, goat manure, chicken manure, and grasshopper manure. The results indicated that there is significant difference on plant height at 30 days after showing (DAS), at age of 80% flowered and at the first harvesting, on age of 80% flowered and age of the first harvesting, and on the fresh fruit production. The best result is attained on the cricket manure treatment (159 g/polybag or 20 tons/hectare).